Antibacterial Activity of Stylissa carteri Sponge Extract from Manado Bay, North Sulawesi - Palungan, Irpan; Bara, Robert Antonius; Mangindaan, Remy Emile Petrus; Kemer, Kurniati; Wullur, Stenly; Rembet, Unstain N. W. J. (Jurnal Ilmiah Platax, 2022)
Marine sponges contain secondary metabolites with unique chemical structures and very interesting pharmacological activities, such as antibacterial, anticancer, antiviral and others to be developed as candidate drugs. The presence of bioactive metabolites in sessile nature such as sponges also reflects the ecological adaptation formed during a long evolutionary process as a defense mechanism of this organism with its environment in the form of resistance to predation, competition and infection factors against pathogenic bacteria, so this study aims to examine the antibacterial activity of extracts and fractions of Stylissa carteri sponge fractions as well as testing the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values. The method used in testing the antibacterial activity is the agar diffusion method (Disc Diffusion Kirby Bauer Method). The presence of antibacterial activity was indicated by the formation of a clear zone around the paper disc after incubation for 24 hours. The results showed that antibacterial activity of S. carteri sponge extract tested on Bacillus megaterium DSM32T bacteria revealed to be the strongest inhibition zone of 21 mm. Further testing on the extract fraction of S. carteri showed that the semipolar fractions showed strong activity against the B. megaterium while the polar fraction was categorized as moderate action, the non-polar fraction showed no activity against the bacteria. The determination of the MIC and MBC values was obtained at 500 ppm and 1000 ppm respectively.